STUDI ANGKA KUMAN AIR KOLAM RENANG DI OWABONG KABUPATEN PURBALINGGA - Faridatul Umaroh; Nurjazuli Nurjazuli; Hanan Lanang Dangiran (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Swimming pool has the potential spread the disease recreation and health problems,therefore quality of swimming pool water must be maintained regularly and continuously so that water can be free from contamination. The purpose of this study was to determine the number of germs in swimming pool water in Owabong Purbalingga Regency. This research was an observational descriptive research with cross sectional approach. The population in this research was water of swimming pool of Owabong Purbalingga Regency while the research sample was olympic pond and child pool were taken by purposive sampling method. Samples of water were taken as many as 6 samples in a day with 3 days of taking a week and done for 2 weeks so that the sample size is 36 samples of swimming pools water. The results showed the average number of germs in the olympic and children swimming pools of 1.5 to 34 colonies / 1 ml sample. The average residual chlor in water of olympic and children swimming pools were 0.15 to 0.11 mg / l. The average pH value in the olympic and children swimming pools were 6.5 to 7.33. The percentage of sanitary condition of the eligible child pool was 73% and the olympic pool was 91%. Overall, the microbial count in the Owabong Swimming Pools water of Purbalingga Regency has been eligible.